Transformasi Tahapan Verifikasi Administrasi dan Faktual Pencalonan Kepala Daerah dalam Yurisprudensi Putusan Mahkamah Konstitusi - Hari Nazarudin; Yuda Adi Kusumah; Muhammad Riefky Alfathan (SIYASI: Jurnal Trias Politica, 2026)
This study aims to answer three research questions: first, how changes to nomination norms following Constitutional Court Decision Number 60/PUU-XXII/2024 and Number 70/PUU-XXII/2024 affect the verification stage conducted by the General Elections Commission (KPU); second, what Decision Number 62/PHPU.BUP-XXIII/2025 means for the standard of examining document accuracy; and third, what legal basis and design of factual verification can be applied without waiting for initial doubt. This research employs normative legal methods with statutory, case, and conceptual approaches, analyzing the three Constitutional Court decisions alongside KPU Regulation Number 8 of 2024. The findings show that Decision Number 60/PUU-XXII/2024 reformulated the nomination threshold to 6.5%–10% of valid votes, while Decision Number 70/PUU-XXII/2024 affirmed that all candidate requirements must be fulfilled before determination. Decision Number 62/PHPU.BUP-XXIII/2025 demonstrates that factual clarification serves as a critical basis for the Court's assessment. The phrase "where doubt exists" in Article 113 of the KPU Regulation does not prohibit proactive factual verification. This study recommends that factual verification of core documents be made a standard obligation, supported by inter-agency data integration, official minutes, digital audit trails, and Election Supervisory Body oversight to prevent nomination disputes.